Comparison of radiofrequency ablation from the coronary cusps and endocardial left ventricular outflow tract for left ventricular summit ventricular arrhythmias in a porcine and infrared thermal model. (23rd January 2022) - Larsen, Timothy; Winterfield, Jeffrey; Ravi, Venkatesh; Du‐Fey‐de‐Lavallaz, Jeanne M.; Wasserlauf, Jeremiah; Trohman, Richard G.; Sharma, Parikshit S.; Huang, Henry D.
Abstract: Introduction: The coronary cusps (CCs) are utilized as an alternative vantage point for radiofrequency catheter ablation (RFCA) of left ventricular summit ventricular arrhythmias but are sometimes a challenge despite favorable activation timing and pace mapping. Methods: Ex vivo experiments were performed in 12 intact porcine hearts submerged in a 37°C saline bath. Radiofrequency (RF) applications were delivered with an irrigated contact force sensing catheter oriented 45° to the endocardial left ventricular outflow tract (LVOT) surface and nadir of the CCs using different dosing parameters. Sections were stained in 2% triphenyltetrazolium chloride and lesion dimensions were measured. Thermal infrared imaging analysis was used to compare time‐to‐lethal tissue temperature and depth/area of lethal isotherms. Results: A total of 60 RF applications were performed under different dosing parameters for (1) 30, 40, and 50  Watts (W) × 30 s and (2) 40 W × 30, 45, and 60 s. Lesion depth was greater with RFCA from LVOT than from the CCs (maximum depth 6.11 vs. 2.68 mm). Longer RF duration led to larger lesion volume in the CC group (40 W × 30 s: 8.1 ± 0.4 vs. 40 W × 60 s: 10.1 ± 0.96 mm; p  = .002). One steam pop occurred in both the LVOT (50 W × 30 s) and CC groups (40 W × 60 s). Time‐to‐reach lethal temperature of 58°C was longer in the CC group than in the LVOT group (4.7 vs. 11.3 s; p  = .02) Conclusions: RFCA from the CC led comparatively to shallower lesion depth than from the LVOT. Longer RF duration led to an increase in lesion volume during ablation from CCs.